2014
DOI: 10.4103/0970-0358.146638
|View full text |Cite
|
Sign up to set email alerts
|

Long term assessment of intralipotherapy in Madelung’s disease

Abstract: Madelung's disease is characterised by multiple symmetric abnormal fat masses in the head, neck and upper limbs. Surgical excision or liposuction is the only realistic available option, although palliative in nature. The serial intralipotherapy with phosphatidylcholine/deoxycholate has been proposed as a non-invasive treatment of Madelung's disease. The authors used serial intralipotherapy with phosphatidylcholine/deoxycholate in two patients affected by Madelung's disease. Three injections per lesion per pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…It was treated surgically without a second recurrence at 32 months of follow-up [ 10 ]. The other two patients ( Table 1 c) had both experienced a successful prior surgical excision [ 18 ]. And this study showed that intralipotherapy achieved a 2.5% reduction in average size and had a 33% recurrence rate [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was treated surgically without a second recurrence at 32 months of follow-up [ 10 ]. The other two patients ( Table 1 c) had both experienced a successful prior surgical excision [ 18 ]. And this study showed that intralipotherapy achieved a 2.5% reduction in average size and had a 33% recurrence rate [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The other two patients ( Table 1 c) had both experienced a successful prior surgical excision [ 18 ]. And this study showed that intralipotherapy achieved a 2.5% reduction in average size and had a 33% recurrence rate [ 18 ]. Medical therapy was described in five reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no studies using ultrasonography for the monitoring of the procedure. Ultrasonography was used only to monitor postoperative edema ( 5 ) , as well as to present treatment outcomes after the use of PC-based preparation compared to two cases of Madelung’s disease ( 17 ) .…”
Section: Discussionmentioning
confidence: 99%
“…A differential diagnosis should be made with: Cushing syndrome; partial familial Dunnigan lipodystrophies (determined by mutations in the LMNA gene); familial angiolipomatosis; simple obesity; neck cysts; lymphoma; leukemia and soft tissue sarcoma; spiradenocarcinoma; and salivary and thyroid gland disease, is necessary [37][38][39][40][41]45,46,50,51]. A biopsy can exclude malignancy or prove the concomitant presence of liposarcoma or an intramyxoid sarcoma [10,14,15,[52][53][54][55][56][57][58][59][60]. Liver disease is a common comorbidity of BSA, and acute renal failure may also occur [10,20,[24][25][26][27][28]50,51].…”
Section: Differential Diagnosis Comorbidities and Malignant Transform...mentioning
confidence: 99%